Transparency and sustainability in the making: A corpus-informed comparative analysis of environmental commitments in airline and railway corporate website discourse - Notari, Fabiola (Comparative Legilinguistics, 2026)
Amid growing pressure on transport companies to demonstrate environmental and social responsibility, this article examines how major airline and railway operators construct “environmental commitments” on their corporate websites. Adopting a corpus-informed, legal-linguistic perspective, it investigates how such commitments are framed and supported within CSR and sustainability communication. The analysis draws on a purpose-built corpus of ≈15,100 words from eight operators (four airlines, four railway companies), consisting of environment- and sustainability-focused webpages (2023–2025). Methodologically, the study combines frequency-based lexical profiling and keyword analysis to map how environmental and sustainability themes are distributed across the AIR and RAIL subcorpora. Concordance-based qualitative analysis then examines how responsibility is linguistically construed along a continuum ranging from commitment-oriented lexis (e.g. commitment, committed, goal, target, ambition) to explicit obligation (e.g. obligation, duty). It also analyses deontic and epistemic modality as well as patterns of agency within a systemic-functional framework. Finally, the study traces legal and quasi-legal references, quantitative baselines and timelines, and third-party validation to assess how far commitments are presented as anchored in external frameworks. Results show that environmental themes occupy a central but differently configured space in both sectors: airline sites foreground climate trajectories, fuel innovation—especially Sustainable Aviation Fuel (SAF)—and global governance frameworks, whereas railway sites emphasise rail’s structurally low-carbon profile, infrastructure management and local socio-environmental benefits. Across both subcorpora, however, the language of commitment and strategic ambition systematically displaces explicit duty: environmental responsibilities are framed less as binding legal obligations and more as voluntary or shared commitments, expressed through soft deontic and prospective modality and dispersed across companies, sectors and technologies. The article argues that, in this genre, credibility relies less on explicit legal obligation than on the density and accessibility of evidential anchors that make commitments publicly traceable while rarely crystallising into clearly enforceable duties.